Designing a Mobile Application for a Healthy Integrated Health Post (Posyandu) for Child Visits and Immunization Services - Kurniawan, Sena; Siti Sarah, Yuni; Oktavia, Nova (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2023)
Maternal and child health care at the Posyandu (Integrated Health Post) is crucial for improving overall community health. Improving optimal health visits, immunizations, and health education, along with effective data and information management, is a challenge. To achieve flexible and effective results, the mobile application was designed using React Native, which offers the advantage of simultaneously developing Android and iOS applications, complemented by an Agile Scrum approach. Therefore, the purpose of this research is to create an innovative and effective mobile application to improve the quality of health services provided at the Posyandu. The design process is organized and tailored to user needs through agile development based on the Scrum model.